The Relationship Between Knowledge About Hypertension and Dietary Patterns Towards the Incidence of Hypertension in Adolescents in Pangarengan Village, Sampang Regency - Mery Eka Yaya Fujianti; Desi Holifatus Su’aida; Ida Wahyuni (Lembaga Pengembangan Kinerja Dosen, 2025)
Hypertension is a non-communicable disease that is no longer limited to the elderly but has also increasingly affected adolescents. The rising prevalence of hypertension among young people requires serious attention due to its long-term health implications. Poor knowledge and unhealthy eating patterns are known to be significant risk factors for hypertension. This study aimed to analyze the relationship between knowledge of hypertension and dietary patterns with the incidence of hypertension among adolescents in Pangarengan Village, Sampang Regency. This research employed a quantitative approach with a cross-sectional design. A total of 30 adolescents were selected using a total sampling technique. The instruments used included a hypertension knowledge questionnaire, a dietary pattern questionnaire using the SQ-FFQ (Semi-Quantitative Food Frequency Questionnaire), and a sphygmomanometer for measuring blood pressure. The results showed that 50% of respondents had good knowledge, and 40% had healthy dietary patterns. The incidence of hypertension was found in 36.7% of respondents, all classified in the prehypertension category. Bivariate analysis using the chi-square test revealed a significant relationship between knowledge and hypertension incidence (p = 0.008), as well as between dietary patterns and hypertension incidence (p = 0.009). The study concludes that there is a significant association between knowledge of hypertension and dietary patterns with the occurrence of hypertension among adolescents. Health education and the promotion of healthy eating habits should be strengthened as preventive strategies from an early age.